Bioremediation of soils contaminated with hydrocarbons by sawdust compost and manure - Buendía R., Hildebrando (2012)
Bioremediation of soils contaminated by hydrocarbons is a technique that involves using living for the consumption of petroleum hydrocarbons in soil organisms. To rule out the reduction of Total Petroleum Hydrocarbons a floor Pampilla Refinery, located at km 25 Window, Window district province of Callao Road. The experiment was installed at Bioassay in Soil Fertility Laboratory of the Universidad Nacional Agraria La Molina, applying the statistical model Experimental Completely Randomized Design (CRD) with three replications and twelve treatments totaling 36 pots experimental, for which manure and sawdust was used as substrate to the indicator plant "maize" (Zea mays L.), seeded and monitored for a period of two months. The results of the dosage of oil contaminated soil, manure and sawdust decreased on average 22.5% of the oil content in the soil, using only manure decreased 16.5% and sawdust using only decreased 9.6%. Comparing the experimental treatments that has better remediated soil was treatment (T3) contaminated soil more Vacaza more sawdust bolaina, since the initial concentration of total petroleum hydrocarbons (TPH) was 21.81 g TPH / kg of soil has decreased by 16.28 g TPH / kg soil, which represents a 25% reduction. This being the most recommended treatment to use.